HMGA2 Antisense Long Non-coding RNAs as New Players in the Regulation of HMGA2 Expression and Pancreatic Cancer Promotion - Ros, Gloria; Pegoraro, Silvia; De Angelis, Paolo; Sgarra, Riccardo; Zucchelli, Silvia; Gustincich, Stefano; Manfioletti, Guidalberto (Frontiers in Oncology, 2020)
Background Natural antisense long non-coding RNAs (lncRNAs) are regulatory RNAs transcribed from the opposite strand of either protein coding or non-coding genes, able to modulate their own sense gene expression. Hence, their dysregulation can lead to pathologic processes. Cancer is a complex class of diseases determined by the aberrant expression of a variety of factors, among them, the oncofetal chromatin architectural proteins High Mobility Group A (HMGA) modulate several cancer hallmarks. Thus, we decided to investigate the presence of natural antisense lncRNAs in HMGA1 and HMGA2 loci, and their possible involvement in gene expression regulation. Methods We used FANTOM5 data resources, FANTOM-CAT genome browser and Zenbu visualization tool, which employ 1829 human CAGE and RNA-sequencing libraries, to determine expression, ontology enrichment and dynamic regulation of natural antisense lncRNAs in HMGA1 and HMGA2 loci. We then performed qRT-PCR in different cancer cell lines to validate the existence of HMGA2-AS1 transcripts. We depleted HMGA2-AS1 transcripts with siRNAs and investigated HMGA2 expression by qRT-PCR and western blot analyses. Moreover, we evaluated cell viability and migration by MTS and transwell assays, and EMT markers by qRT-PCR and immunofluorescence. Furthermore, we used bioinformatics approaches to evaluate HMGA2 and HMGA2-AS1 correlation and overall survival in tumor patients. Results We found the presence of a promoter-associated lncRNA (CATG00000088127.1) in the HMGA1 gene and three antisense genes (RPSAP52, HMGA2-AS1, and RP11-366L20.3) in the HMGA2 gene. We studied the uncharacterized HMGA2-AS1 transcripts, validating their existence in cancer cell lines and observing a positive correlation between HMGA2 and HMGA2-AS1 expression in a cancer-derived patient dataset. We showed that HMGA2-AS1 transcripts positively modulate HMGA2 expression and migration properties of PANC1 cells through HMGA2. In addition, Kaplan-Meier analysis showed that high level of HMGA2-AS1 is a negative prognostic factor in pancreatic cancer patients. Conclusions Our results describe novel antisense lncRNAs associated with HMGA1 and HMGA2 genes. In particular, we demonstrate that HMGA2-AS1 is involved in the regulation of its own sense gene expression, mediating tumorigenesis. Thus, we highlight a new layer of complexity in the regulation of HMGA2 expression, providing new potential targets for cancer therapy.